VINASSE FROM THE BRAZILIAN LIGNOCELLULOSIC ETHANOL PROCESS: CHEMICAL COMPOSITION AND POTENTIAL FOR BIOPROCESSES - Souza Silverio, Manuella; Perez Calegari, Rubens; Ferreira Lima Leite, Gabriela Maria; Maciel Lewandowski Meira Prado, Laysa; Chaves Martins, Bianca; Alberto da Silva, Eric; Piotrovski Neto, José; Gomig, André; Sampaio Baptista, Antonio (Revista Brasileira de Engenharia de Biossistemas, 2021)
Brazil is the second-largest producer of ethanol and the alcoholic fermentation wastes have become a concern for both environmental and economic reasons. Recently, the Brazilian industry has implemented the second generation (2G) process to attend the growing for biofuel. In this study, we aimed to investigate whether the 2G vinasse faces the same environmental challenges that first generation (1G) vinasses do, meaning vinasses from ethanol processes using sugarcane juice and/or molasses. Thus, vinasse was obtained from one of the recently-started 2G ethanol facilities in São Paulo State and then chemically characterized. Considering glycerol, mannitol, residual sugars, and organic acids concentrations altogether, it was determined that 2G vinasse had a total carbon source of 23,050 mg L-1 (compared to 4,800 mg L-1 in 1G vinasse). Magnesium, calcium, potassium, and others salts were determined as well. Based on its chemical composition, vinasses could be considered as nutrient sources for other bioprocesses. Finally, we brought some perspectives into bioprocesses with nutritional requirements that might be fully or partially provided by vinasses, leading to the production of bioenergy or bioproducts.